Law Enforcement On Combating Crime Of Motorized Vehicle Theft In Jurisdictions Police Central (Case Study To Be Treated By Central Java Police) - Wahyu Adhi Admaja; Gunarto Gunarto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The purpose of this research is 1) To review and analyze law enforcement on the eradication of theft of motor vehicles in the jurisdiction of the Central Java Police. 2) To analyze the factors that affect law enforcement on the eradication of theft of motor vehicles in the jurisdiction of the Central Java Police. 3) To formulate a law enforcement solution to the eradication of theft of motor vehicles in the jurisdiction of the Central Java Police in the future. The method used in this research is using empirical juridical and sociological law research can be named after the field research, including reviewing the applicable law and what happens in reality in society. In this study, the law conceived as an empirical phenomenon that can be observed in real life. The results of the research concluded that: 1) The enforcement of the law against eradication of theft of motor vehicles in the jurisdiction of the Central Java Police to control or solve crimes (political criminals) use two (2) means, namely: a) Means non penal is enforcement of the law against acts criminal use non penal facility includes the use of social means to improve certain social conditions, but indirectly affect efforts to prevent crime. b) Means Means penal penal is crime prevention with the use of criminal law 2) Factors that affect law enforcement on the eradication of theft of motor vehicles in the jurisdiction of the Central Java Police consists of internal and external factors. Internal factors are occurring of itself, while the external factor is a factor that is created from outside himself, these factors can be quite complex and varied. Social inequality, economic inequality, injustice, etc., are examples of the causes of crime originating from outside himself. 3) The enforcement of the law against eradication of theft of motor vehicles in the jurisdiction of the Central Java Police in the future is to optimize the investigation, effective and efficient course correction, through changes above are expected to materialize figure investigator professional, clean, dignified and beloved people are protected, be acknowledged and serviced. Such measures are reflected in the personal integrity of each investigator maid intact. Keywords: Law Enforcement; Eradication; Motor Vehicle Theft.